Safety Enhancement of Tehran Research Reactor with a Second Shutdown System - E Boustani; S Khakshournia; E Abedi (مجله علوم و فنون هسته‌ای, 2017)
Safety and related categories are of importance in all fields of nuclear industry, especially as regards the nuclear reactors. One of the most important safety aspects in the nuclear reactors is the shutdown system, each reactor requiring at least one. One of capabilities that can improve the safety of a nuclear reactor is adding another shutdown system to it. For making any change as design and locating second shutdown system in the reactor, attention to special characteristics of any reactor and design basis criteria such as redundancy, diversity, separation, single failure criteria and fail-safe mode is necessary. A second shutdown system based on the injection of neutron absorber is designed with considering its standards and requirements for Tehran Research Reactor. The proposed design has a high reliability that fulfils the most important design requirement, which is having enough negative reactivity, has the ability to maintain the reactor in subcritical state in a determined period of time with the necessary safety margin and for needed time duration. Calculations and simulations have been done using MCNPX code. This design has some negative effects on different core characteristics, albeit minimized by the designed structure optimization.